European projects related to ethical education in primary and secondary schools - Ćurko, Bruno (Array, 2019)
Through the Erasmus+ Program, in Key Activity 2 – “Strategic Partnerships in Education and Training” (KA2) – association for promotion of non-formal education, critical thinking and philosophy in practice “Petit Philosophy” has implemented or is implementing seven projects closely related to ethical education. The characteristics of these projects are that they are directed to ethical education in kindergartens and primary and secondary schools. Partners of “Petit Philosophy” in these projects were/are universities, primary and secondary schools, kindergartens, associations and institutions from thirteen countries (Austria, Germany, Slovenia, Italy, Spain, Hungary, Bosnia and Herzegovina, Greece, Ireland, the Netherlands, Slovakia, Latvia and Croatia). Project “ETHOS: Ethical Education in Primary and Pre-primary Schools for a Sustainable and Dialogic Future” is one of the first of these projects. ETHOS was successfully implemented under the Comenius Program from 2012–2014, and afterwards, projects under the Erasmus+ KA2 followed: ETHIKA – Ethics and Values Education in Schools and Kindergartens (2014–2017), LITTLE – Learning Together to Live Together: Teachers Leading Ethical Education for an Inclusive Society (2016–2019), AVAL – Added Value Learning for Preschool Teachers & Pedagogical Coordinators (2017–2019), COMET – A Community of Ethics Teachers in Europe (2017–2020), Integrating Ethics of Sport in Secondary School Curriculum (2017–2019), BEAGLE – Bioethical Education and Attitude Guidance for Living Environment (2018–2020) and TRACE – Traditional Children’s Stories for a Common Future (2018–2020). In this article, we will briefly present the projects’ activities, with particular emphasis on materials created for educators, teachers, and students.